STRATEGI PEMASARAN PENDIDIKAN DALAM MENARIK MINAT CALON SISWA DI ERA DIGITAL STUDI KASUS DI SDN 8 SUMBERAGUNG - Mufasirul Bayani; Sidiq Purnomo (CV. ADIBA AISHA AMIRA, 2025)
This study aims to analyse the implementation of digital-based education marketing strategies at SDN 8 Sumberagung and its impact on increasing the interest of prospective students. The method used is qualitative research with a case study approach, which allows researchers to explore in depth the digital marketing practices implemented by the school. Data collection techniques included in-depth interviews with the principal, teachers, parents and alumni, as well as participatory observation of the school's social media activities. Secondary data, such as student enrolment reports and social media visit statistics, were also used to complete the analysis. Data analysis techniques were conducted using thematic analysis to identify patterns and main themes that emerged from the collected data. The results showed that effective use of social media, such as Facebook and Instagram, has increased the school's visibility, strengthened relationships with parents, and increased the number of new registrants by almost 30%. Attractive visual content also proved to be effective in increasing community engagement and expanding the school's promotional reach. Overall, the social media-based digital marketing strategy at SDN 8 Sumberagung has successfully improved the school's image and attracted more new applicants.